1+sqrt(x+5)=sqrt(2x+5)

Simple and best practice solution for 1+sqrt(x+5)=sqrt(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+sqrt(x+5)=sqrt(2x+5) equation:


Simplifying
1 + sqrt(x + 5) = sqrt(2x + 5)

Reorder the terms:
1 + qrst(5 + x) = sqrt(2x + 5)
1 + (5 * qrst + x * qrst) = sqrt(2x + 5)
1 + (5qrst + qrstx) = sqrt(2x + 5)

Reorder the terms:
1 + 5qrst + qrstx = qrst(5 + 2x)
1 + 5qrst + qrstx = (5 * qrst + 2x * qrst)
1 + 5qrst + qrstx = (5qrst + 2qrstx)

Add '-5qrst' to each side of the equation.
1 + 5qrst + -5qrst + qrstx = 5qrst + -5qrst + 2qrstx

Combine like terms: 5qrst + -5qrst = 0
1 + 0 + qrstx = 5qrst + -5qrst + 2qrstx
1 + qrstx = 5qrst + -5qrst + 2qrstx

Combine like terms: 5qrst + -5qrst = 0
1 + qrstx = 0 + 2qrstx
1 + qrstx = 2qrstx

Solving
1 + qrstx = 2qrstx

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2qrstx' to each side of the equation.
1 + qrstx + -2qrstx = 2qrstx + -2qrstx

Combine like terms: qrstx + -2qrstx = -1qrstx
1 + -1qrstx = 2qrstx + -2qrstx

Combine like terms: 2qrstx + -2qrstx = 0
1 + -1qrstx = 0

Add '-1' to each side of the equation.
1 + -1 + -1qrstx = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -1qrstx = 0 + -1
-1qrstx = 0 + -1

Combine like terms: 0 + -1 = -1
-1qrstx = -1

Divide each side by '-1rstx'.
q = r-1s-1t-1x-1

Simplifying
q = r-1s-1t-1x-1

See similar equations:

| (12a^4b-7a^2b^2+8ab^3)+(-6a^4b-5a^2b^2+3ab^3)= | | 2x-4+7=3 | | (x-4)(x-8)=5 | | 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 | | K+6K-13=57 | | 3x*3x-2x+7=0 | | 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 | | 3x+12=9x+39 |

Equations solver categories